2001 Philippine statistical yearbook. - Philippines. National Statistical Coordination Board (Makati City NSCB, 2001)
Purpose: The book "presents in time series, statistics about the country's macro and micro environment and contain data which are disaggregated in different dimensions as useful tools in the conduct of feasibility studies, strategic planning and socio economic policy decision making".
This includes statistics about the country's macro and micro environment. It also contains data regarding useful tools in the conduct of feasibility studies, strategic planning and socio economic policy decision-making.
Contents: Table of figure references. List of data sources. Population. Income. Environment and natural resources. Agriculture. Tourism. Health. Education. Labor and employment. Transportation. Energy. Banking. Public administration. Peace and order. Science and technology. International statistics. Appendix.
1974-1987 entered under: Philippines (Republic). National Economic Development Authority ; 1974-1977 has title: NEDA statistical yearbook.
Keywords: Philippines -- Statistics